EVALUATION AND UPSCALING OF ZERO TILLAGE MAIZE (Zea mays L.) – A RESOURCE CONSERVATION TECHNOLOGY IN ANDHRA PRADESH - RAO; K. ANAND SINGH, K. DATTATRI, G. RAJENDER REDDY, N. SUDHAKAR, A.R.REDDY, N. VENKATESHWAR (The Journal of Research, PJTSAU, 2017)
In Andhra Pradesh rabi maize yields in kharif rice fallows were affected due to late sowing under traditional practice of sowing after preparatory tillage. The crop was also subjected to terminal moisture stress due to late sowing in command areas particularly in tail end areas. To overcome the above situation zero tillage maize technology was introduced in Andhra Pradesh through KVKs. On farm trials and front line demonstrations were organized by KVKs in Andhra Pradesh to test and promote zero tillage maize technology during 2007-08 to 2011-12. The results revealed that there was a decrease in the cost of cultivation to an extent of Rs.3969/ha and an additional net returns of Rs.4119/ha was obtained by adopting zero tillage maize technology besides about 9 percent increase in yield as compared to conventional method. Due to the efforts made by the KVKs in convergence with other departments about 19000 ha of rabi maize was brought under this technology.